Evaluation of human sperm chromatin status after selection using a modified Diff-Quik stain indicates embryo quality and pregnancy outcomes following in vitro fertilization - Tavares, R. S. (2013)
Sperm chromatin/DNA damage can be measured by a variety of assays. However, it has been reported that these tests may lose prognostic value in Assisted Reproductive Technology (ART) cycles when assessed in post-prepared samples, possibly due to the normalizing effect promoted by sperm preparation procedures. We have recently implemented a modified version of the Diff-Quik staining assay that allows for the evaluation of human sperm chromatin status in native samples, together with standard sperm morphology assessment. However, the value of this parameter in terms of predicting in vitro fertilization (IVF) and Intracytoplasmic sperm injection (ICSI) outcomes after sperm selection is unknown. In this study, data from 138 couples undergoing in vitro fertilization (IVF) or Intracytoplasmic sperm injection (ICSI) treatments showed that sperm chromatin integrity was significantly improved after density gradient centrifugation and swim up (p < 0.001), but no correlations were found with fertilization or embryo development rates (p > 0.05). However, sperm samples presenting lower percentages of damaged chromatin were associated with better quality (Grade I) embryos in both ART procedures (p < 0.05) and clinical pregnancy among IVF couples (p < 0.05). Furthermore, regression analysis confirmed the clinical value of Diff-Quik staining in predicting IVF (but not ICSI) clinical pregnancy (OR: 0.927, 95% CI: 0.871–0.985, p = 0.015), and a threshold value of 34.25% for this parameter was established. The proportion of IVF couples achieving a clinical pregnancy was reduced 1.9-fold when the percentage of abnormal dark staining was ≥34.25% (p = 0.05). In conclusion, the Diff-Quik staining assay provides useful information regarding ART success, particularly in IVF cycles, where some degree of ‘natural’ sperm selection may occur; but not in ICSI, where sperm selection is operator dependent. This quick and low-cost assay is suggested as an alternative method to detect sperm chromatin status in minimal clinical settings, when no other well-established and robust assays (e.g. Sperm chromatin structure assay, terminal deoxynucleotidyl transferase-mediated dUDP nick-end labelling) are available.